Impact of Buried Conductor Length on Computation of Earth Grid Resistance - S. D. Buba; W. F. Wan Ahmad; Mohammed Z. A. Ab Kadir; C. Gomes; J. Jasni; M. Osman (Institute of Advanced Engineering and Science, 2015)
Effective design of substation earth grid implies achieving low earth grid resistance and fulfillment of the safety criteria at the lowest possible cost. This paper presents an evaluation of IEEE Standard 80-2000 Equations 50 to 52 to determine the impact of buried conductor length on computation of earth grid resistance. Calculated results indicated that a saturation point is reached beyond which further addition of more conductor length does not significantly reduce the earth grid resistance but incurs more economic implications. These were validated by earth grids designed using CDEGS where good agreement between the calculated and simulated results was found.